Design of an Intelligent Active Surveillance and Early Warning System for Infectious Diseases - Min Liu; Wannian Liang; Jian Hu; Liangyu Kang; Wenzhan Jing; Kangning Cai; Xiaopeng Qi; Debing Liu; Quanyi Wang (中国工程科学)
Developing an intelligent active surveillance and early warning system for infectious diseases is crucial for responding to major infectious disease outbreaks, advancing surveillance technologies, and enhancing monitoring and warning capabilities. An intelligent active surveillance and early warning system is also essential for realizing the scientific, timely, and accurate monitoring and early warning of major infectious disease outbreaks. This study examines the necessity of establishing an intelligent active surveillance and early warning system for infectious diseases, outlines the current status and existing problems of infectious disease surveillance and early warning systems both in China and abroad, and proposes a design framework for the intelligent active surveillance and early warning system for infectious disease outbreaks. The proposed system encompasses four key functional modules: multi-channel active surveillance, intelligent early warning, data-driven risk assessment, and smart response and evaluation. Progress has been made in developing critical technologies such as multi-source data fusion, intelligent early warning, multidimensional risk assessment, and smart disposal evaluation, thus providing a solid technical foundation for the system's construction and application. In the future, continued multidisciplinary collaboration is required to progressively establish and optimize this system, and this system will provide more effective tools for preventing and controlling the spread of major and emerging infectious diseases.